Gut Bacterial Flora of Open Nested Honeybee, Apis florea - Ganeshprasad, D. N.; Lone, Jafar K.; Jani, Kunal; Shouche, Yogesh S.; Khan, Khalid Ali; Sayed, Samy; Shukry, Mustafa; Dar, Showket A.; Mushtaq, Muntazir; Sneharani, A. H. (Frontiers in Ecology and Evolution, 2022)
Honey bees are eusocial insect with close interaction to their surrounding environment. Gut microbiota in honey bees have a significant role inhost health, biology and interaction behavior with surrounding environment. Apis florea, a wild bee, is the most primitive among all honey bees and is indigenous to the Indian subcontinent. Previous reports on rearedhoney bee species provide information on gut microbiome. No such studies are reported on the gut microbiota of the wild honey bee species. The present study is aimed in studying gut microbiome in wild species of honey bee, viz. Apis florea.The study reports the analysisand identification of gut bacteria in the wild species of honey bee, Apis florea, employing culture-based and culture-independent methods. Cultured bacteria were identified and characterized by MALDI-TOF MS and 16S rRNA sequencing. A comprehensive analysis and identification of non-culturable bacteria were performed by 16S rRNA amplicon next-generation sequencing. This approach splits gut bacteria into fourbacterial phyla, fourfamilies and 10 genera in major. The dominant taxa identified in Apis florea belonged to familyEnterobacteriaceae (79.47%), Lactobacillaceae (12.75%), Oxalobacteraceae (7.45%) and Nocardiaceae (0.13%). The prevailing bacteria belonged to the genera of Enterobacter,Lactobacillus, Escherichia-Shigella, Massilia, Klebsiella, Citrobacter, Pantoea, Serratia, Rhodococcus and Morganellabelonging to phyla Proteobacteria, Firmicutes, Actinobacteriaand Bacteroidetes. This study made an observation of occurrence of few bacteria which are not previously reported for their occurrence in other species of Apis genus making this investigation highly relevant with regard to bee microbiome.